Nanoengineering of amino - functionalized mesoporous silica nanospheres as nanoreactors - Gao, J.; Wu, S.; Tan, F.; Tian, H.; Liu, Jian; Lu, G. (Elsevier Ltd, 2018)
© 2018 Selective functionalization of mesoporous silica nanospheres (MSNs) is crucial for nanoengineering of MSNs. Herein, we have combined “surface-protected etching strategy” and “cationic surfactant assisted etching strategy” to prepare functionalized MSNs with externally attached amino groups. The externally attached NH 2 groups endow the catalysts with excellent catalytic performance for nitroaldol reaction between nitromethane and benzaldehyde. In addition, those NH 2 -MSNs can also be used to support gold nanoparticles, which display very good catalytic performance for reduction of 4-nitrophenol. It can be envisioned that the synthesis protocol developed in this work could also be extended to nanoengineered MSNs, which provides opportunities for nanoreactors design.